E-MARKETPLACE FOR SMEs IN TOURISM VILLAGES - Intan oktaviani; Eko Purwanto; Indah Nofikasari (LPPM Universitas Duta Bangsa Surakarta, 2022)
The Ngargoyoso tourist attraction area is one of the popular tourist attractions in Karanganyar Regency, especially in Central Java. In this tourist area there are many small and medium enterprises (SMEs) that offer various products, especially original products from Ngargoyoso. The use of information technology to support the marketing and promotion of local products, namely the Electronic Marketplace which is made based on a website with marketing and sales features, is expected to increase income and improve the welfare of the local community. The problem faced by Small and Medium Enterprises in the Ngargoyoso Tourism Village area is that the sales model that is carried out is still conventional and the promotions carried out are still very limited, only limited to the surrounding area. Sometimes tourists who visit don't even know the location of the SMEs in the tourist village of Ngargoyoso. And also many tourists who don't know what products from SMEs and their locations are, considering that currently in the tourist village of Ngargoyoso there is no market or physical store to market souvenirs typical of the products of SMEs in the village of Ngargoyoso. This has resulted in several SME products that have not been exposed to the outside. Even though during the COVID-19 pandemic, such as the current number of tourists visiting the Ngargoyoso tourist village, of course this greatly affects the income value of SMEs in the Ngargoyoso tourist village. Thus, the application of the Electronic Marketplace with a Rule Based Expert System can be used as a promotional media and selling and buying with a wider reach.